Empresariamento da vida: discurso gerencialista e processos de subjetivação - Ambrózio, Aldo (2011)
This study seeks to undertake an archeology of the managerialist discourse as well as a cartography of the dispositifs which sustained the implications of power in the social field. The intensification of an entrepreneurializement (empresariamento) process during the 1980s and 1990s is examined. The materiality of such process is the organizing constitution of the imperial architecture command conjugated with a type of capital accumulation in which the primacy of financial capital prevails over its other manifestations (productive capital, merchant capital, interest capital). This culminates in the deepening internationalization of money flows, the shortening of the useful life of goods and the primacy of immaterial labor over other types of work which is the intensive source of the imperial structure. The study also analyzes a simultaneous process to the one mentioned above. On one hand, there was a deeper capture of life by power dispositifs. On the other, the liberation of life into multiple directions and senses. The link between the neoliberal governmentality which expresses the imperial architecture command and the managerialist discourse expansion into the social body is one in which this discourse serves as a modulator of the subjectivities captured by the interventionist framework of the neoliberal State. That converts the wandering and differentiating dynamics of a life into a cage called human capital. In other words, modulations of individual lives become capitalists of the self. Therefore, this study denominates the process of capturing and converting the innumerable erratic paths of a life into strategies of personal capitalization as the entrepreneurializement of life